2019
DOI: 10.3390/agronomy9110706
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Interactions between Biomass, Grain Production and Grain Protein Content in High and Low Protein Wheat Genotypes under Controlled Environments

Abstract: Grain protein content (GPC) is a key quality attribute and an important marketing trait in wheat. In the current cropping systems worldwide, GPC is mostly determined by nitrogen (N) fertilizer application. The objectives of this study were to understand the differences in N response between high and low GPC wheat genotypes, and to assess the value of biomass growth analysis to assess the differences in N response. Six wheat genotypes from a range of high to low GPC were grown in low, medium and high N, under g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
(97 reference statements)
2
9
0
Order By: Relevance
“…The NVT data show that a 1 t/ha increase in yield leads to an average GPC loss of 0.45% and 1.63% in ET0 and ET4, respectively. Previous studies on wheat also found a stronger negative relationship between yield and GPC under low N compared to high N supply [20,33,51]. The strong GPC-yield trade off under low N conditions can be due to a higher priority for the plants to maintain grain number and weight than for grain protein accumulation.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The NVT data show that a 1 t/ha increase in yield leads to an average GPC loss of 0.45% and 1.63% in ET0 and ET4, respectively. Previous studies on wheat also found a stronger negative relationship between yield and GPC under low N compared to high N supply [20,33,51]. The strong GPC-yield trade off under low N conditions can be due to a higher priority for the plants to maintain grain number and weight than for grain protein accumulation.…”
Section: Discussionmentioning
confidence: 88%
“…In order to assess the reliability of the ET effects on yield and GPC, six varieties were examined and compared to the full dataset (Figures 4 and 5). The same varieties were used previously to examine their responses to N application in a controlled environment where plant growth rates were assessed [33]. In the previous study, it was found that the severity of stress, in that case the stress was induced through N starvation, intensified the negative relationship between yield and GPC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations